Characterization of users of adult Intensive Care Units and Coronary Care Units in the city of Pelotas/RS - Lunelli , Luiza Henriques; Spagnolo , Lilian Moura de Lima; Michielin , Fabiano da Costa; Machado , Elisiane de Oliveira; Wachter , Djulia Andriele; Santos, Suimara; Chassot , Maicon Daniel; Vizini , Simone Thais; Rosa, Fabio Silva da; Reis, Fernanda dos; Neves, Josiele de Lima (Seven Editora, 2024)
This research aimed to characterize users of Adult Intensive Care Units and Coronary Care Units in the city of Pelotas/RS during hospitalization in 2020. To this end, a quantitative, descriptive research with a cross-sectional design was undertaken. This is an excerpt from the database of the study “Family Satisfaction with Care in the Intensive Care Unit -FS-ICU 24R: Cross-cultural adaptation and validation for Brazilian Portuguese”. Data were collected between 2018 and 2022. The variables of interest available in the research database were analyzed, totaling 222 medical records. The data processed and stored in the Statistical Package for the Social Sciences program were transferred to Stata 17.0 Software, in which descriptive statistics were applied with distribution of absolute and relative frequencies, measures of central tendency and dispersion. The results identified that 51.8% (115) of users were male, 91% (202) were white, and the elderly age group was predominant with 61.7% (137). Regarding the presence of comorbidities, at least one type was identified in 66.7% (148) of users, clinical admission was the majority in 81.5% (181) of hospitalizations. Regarding the reason for hospitalization, the main cause was Acute Coronary Syndrome in 45.1% (100) of users, the majority (60.4%; 134) were not subjected to Invasive Mechanical Ventilation. Most users remained hospitalized for up to 7 days (67.5%; 150), and the discharge outcome was predominant (72.5%; 161). As for predictors of death, female users, who were subjected to invasive mechanical ventilation, hospitalized for a period between 21 and 28 days and admitted due to a stroke or oncological reasons, had a higher percentage of mortality. The study concluded that the results of this research bring a contribution to the area of knowledge, in order to improve the quality of care provided and also to identify the main weaknesses in assistance through understanding the mortality profile. DOI:https://doi.org/10.56238/sevened2024.001-032